A comparison of the effects of energy management using heat pump water heaters and batteries in photovoltaic -installed houses. (15th September 2017) - Iwafune, Yumiko; Kanamori, Junichiro; Sakakibara, Hisayoshi
Highlights: The demand response effect using heat pump water heaters (HPWHs) is examined. Actual electricity consumption data obtained from 357 houses is analyzed to evaluate the demand response effect. The increase in the self-consumption ratio of photovoltaic systems is estimated using HPWHs and batteries. The effect of the optimization of HPWH operation is equivalent to a 2–4 kW h battery. Optimization of HPWH operation contributes to electricity conservation. Abstract: This study examines the economic effects of demand response management using heat pump water heaters (HPWHs) and batteries with residential photovoltaic (PV) systems. A model was developed for optimizing the operation of HPWHs using 24 h advance forecasting of electricity consumption and PV generation. The goal was to minimize electricity charges by optimizing the operation of actual HPWHs. Annual electricity consumption data from 357 houses fitted with both PV and an HPWH were used in the study. Optimal operation of an HPWH was shown to yield average cost savings of 58 or 7% of the electricity cost in conventional operation. HPWH electricity consumption was reduced by 11% on average, compared with conventional operation, because running the heat pumps during the daytime increases their efficiency. A simple modification, in which the start of HPWH operation depended on the level of available sunlight, yielded a comparable average saving of 53 per year. A comparison was made with the use of battery systems. The self-consumption ratio increased from 32% in conventional operation to 45% by optimizing the operation of the HPWH, which was similar to the effect of introduction of a 2–4 kW h battery. The simulation results show that the demand response of HPWHs contributes to the expansion of self-consumption of PV systems and energy conservation.